Toceranib phosphate in the treatment of canine thyroid carcinoma: 42 cases (2009‐2018). (13th February 2020) - Sheppard‐Olivares, Sabina; Bello, Nora M.; Wood, Elizabeth; Szivek, Anna; Biller, Barbara; Hocker, Samuel; Wouda, Raelene M.
Abstract: Thyroid carcinoma is the most common endocrine malignancy in dogs. Thyroidectomy and radiation therapy control local disease, yet are not always feasible, and efficacious medical therapies need to be identified. Toceranib phosphate has been reported to provide clinical benefit (CB) in dogs with thyroid carcinoma, while its role in treatment‐naïve thyroid tumours has not been well‐described. The objective of this study was to describe the use of toceranib in the management of thyroid carcinomas in dogs in both the naïve‐disease and prior therapy‐ settings. A medical record search identified 42 dogs diagnosed with thyroid carcinoma and treated with toceranib, of which 26 and 16 dogs were in settings of naïve‐disease and after prior therapy, respectively. Twenty‐three (88.4%) and twelve (75%) dogs experienced CB in the naïve and prior therapy settings, respectively. The median [95% confidence interval] progression free interval (PFI) for dogs in the naïve and prior therapy settings were 206 [106, 740] and 1015 [92, 1015] days, respectively. The median overall survival time (OST) for dogs in the naïve and prior therapy settings were 563 [246, 916] and 1082 [289, 1894] days, respectively. Overall, the data provided no evidence for differences in overall PFI ( P > .20) or OST ( P = .15) between settings. However, when asymptomatic at the time of diagnosis, dogs in the naïve setting showed poorer survival prognosis (estimated hazard ratio 17.2 [1.8, 163]) relative to dogs in the prior therapy setting. This study characterizes PFI, OST and CB with minimal AE in dogs with thyroid carcinoma treated with toceranib in both the naïve and prior therapy settings.